Performance Comparison of an OTA Using Vertical Nanowire FET in Forward and Reverse Modes - Ribeiro, Arllen D. R.; Silva, Vanessa C.P.; Martino, Joao A.; Agopian, Paula G. D. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2025)
This paper presents a comparative performance of a two-stage transconductance operational amplifier (OTA) implemented with vertical nanowire field-effect transistors (VFETs) in forward and reverse operating modes. Experimental data from VFET were used to model the device with Verilog A approach. The OTA circuit was simulated using Cadence and it was obtained that the voltage gain (AV), 44 dB in forward mode vs. 22 dB in reverse mode, gain bandwidth product (GBW), 65 MHz vs. 99 MHz, and power dissipation, $46 \mu \mathrm{W}$ vs. $96 \mu \mathrm{W}$. The results indicate that forward mode provides higher voltage gain due to lower output conductance, while reverse mode achieves superior GBW due to the higher transconductance. Additionally, an optimized design reducing the compensation capacitor in reverse mode significantly increased GBW to 325 MHz while maintaining stability with a 63° phase margin. These results contribute to the design of highefficiency analog circuits utilizing VFET technology.